Audio-Description - Benecke, Bernd (Meta)

(untitled) (Les Presses de l'Université de Montréal, 2004)
AbstractThis paper deals mainly with two aspects of audio-description: the development of this mode of language transfer and the main steps in the preparation of an audio-description.